Clavulanic acid production processes in a tower bioreactor with immobilised cells - Lavarda, Susana C. S. [UNESP]; Hokka, Carlos O.; Araujo, Maria Lucia Gonsales da Costa [UNESP] (Elsevier B.V. Sa, 2008)
The feasibility of using Streptomyces clavuligerus ATCC 27064 bioparticles supported on alginate gel containing alumina to produce clavulanic acid (CA) was investigated. To this end, effectiveness factors for spherical bioparticles, relating respiration rates of immobilised and free cells, were experimentally determined for various dissolved oxygen (DO) levels and bioparticle radii. Monod kinetics was assumed as representative of the oxygen consuming reaction, while internal oxygen diffusion was considered the limiting step. A comparison was made of the results from a tower bioreactor operating under batch, repeated-batch and continuous conditions with immobilised bioparticles. The theoretical curve of the effectiveness factor for the zero-order reaction model, considering an inert nucleus - the dead core model - was very well fitted to the experimental data. The results of the bioprocess indicated that the batch operation was the most efficient and productive, requiring a do concentration in the reactor above 60% of the saturation value. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: clavulanic acid; immobilised Streptomyces; tower bioreactor; oxygen transfer; diffusion-reaction; effectiveness factor